(3eJWdHGJ JWHjb CHYGO GdbjGOI GdJfehjI ai eOGQS GdJYdje GdCSGSi HeUQ (B/s - (3,YaGa YHO GdeMSf EHQGgje Zfjes; (3CeGfj YHO GdbGOQ eMeO TYHGf s; (3SGQI YHO Gdehdi GdeJhdi EHQGgjes (2024)
(3gOaJ GdOQGSI Edi JYQa eJWdHGJ JWHjb CHYGO GdbjGOI GdJfehjI aj eOGQS GdJYdje GdCSGSj HeUQ, hGdcTa Yf Cge GdNHQGJ GdYGdejI aj eLGd JWHjb GdbjGOI GdJfehjI HeDSSGJ GdJYdje GdCSGSj, ceG gOaJ Edi JYQa hGbY eeGQSGJ CHYGO GdbjGOI GdJfehjI aj eOGQS GdJYdje GdCSGSj HeUQ, hJbOje JUhQ ebJQM deJWdHGJ JWHjb CHYGO GdbjGOI GdJfehjI aj eOGQS GdJYdje GdCSGSj HeUQ, hGYJeOJ GdOQGSI Ydi GdefgL GdeNJdW (B((3Gdcej hGdcjaj(B)(3, aGSJNOeJ GdESJHGfI hGdebGHdI GdTNUjI cCOhGJ dLeY GdHjGfGJ hGdeYdheGJ, hJe JWHjb GdESJHGfI Ydi YOO (B(388) (3eYde, hCLQjJ GdebGHdI GdTNUjI eY(B(21) (3eOjQ,(B(9) (3hcjd aj eOGQS GdJYdje GdCSGSj aj cd ef EOGQGJ (B((3GdSGMd hQhV GdaQL hGdfRgI hTQb eOjfI fUQ(B) (3GdJYdjejI, hbO JhUdJ GdOQGSI Edi YOO ef GdfJGFL ef CgegG(B: (3Ef JWHjb CHYGO GdbjGOI GdJfehjI dG jQJbj Edi GdeSJhi GdeCehd Ydi GdeSJhi GdEOGQj hGdJYdjej, hVQhQI Gdhbha Ydi GdBdjGJ GddGReI dJWHjbgG, hVYa GdehGQO GdeGOjI GdeJGMI GddGReI dJWhjQ hJfejI GdeYdejf, hVYa ETQGc bGFO GdeOQSI ddeYdejf aj YedjJj UfY hEJNGP GdbQGQGJ, hVYa JTLjYge Ydi GdJYde GdeSJeQ eOi GdMjGI(B. s
The study aimed to identify the requirements for applying the dimensions of developmental leadership in basic education schools in Egypt, and to reveal the most important international experiences in the field of applying developmental leadership in basic education institutions. It also aimed to identify the reality of practices of the dimensions of developmental leadership in basic education schools in Egypt, and to present a proposed vision for the requirements for applying the dimensions of developmental leadership in basic education schools in Egypt. The study relied on the mixed approach (quantitative and qualitative), so the questionnaire was used Personal interview as tools for collecting data and information, the questionnaire was applied to (388) teachers in basic education schools in Egypt, and personal interview was conducted with (21) principals, (9) deputies in primary schools in each of the educational administrations (Al-Sahel, Rod El-Farag, El-Nozha and East Nasr City).
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B153-163.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJYdje GdCSGSjs; (3GdbjGOI GdJfehjI s -- (3eDSSGJ GdJYdje GdCSGSjs